Socioeconomic status, white matter, and executive function in children. Issue 10 (2nd August 2016) - Ursache, Alexandra; Noble, Kimberly G.; ,
Abstract: Background: A growing body of evidence links socioeconomic status (SES) to children's brain structure. Few studies, however, have specifically investigated relations of SES to white matter structure. Further, although several studies have demonstrated that family SES is related to development of brain areas that support executive functions (EF), less is known about the role that white matter structure plays in the relation of SES to EF. One possibility is that white matter differences may partially explain SES disparities in EF (i.e., a mediating relationship). Alternatively, SES may differentially shape brain‐behavior relations such that the relation of white matter structure to EF may differ as a function of SES (i.e., a moderating relationship). Method: In a diverse sample of 1082 children and adolescents aged 3–21 years, we examined socioeconomic disparities in white matter macrostructure and microstructure. We further investigated relations between family SES, children's white matter volume and integrity in tracts supporting EF, and performance on EF tasks. Results: Socioeconomic status was associated with fractional anisotropy (FA) and volume in multiple white matter tracts. Additionally, family income moderated the relation between white matter structure and cognitive flexibility. Specifically, across multiple tracts of interest, lower FA or lower volume was associated with reduced cognitive flexibility among children from lower income families. In contrast, children from higher income families showed preserved cognitive flexibility in the face of low white matter FA or volume. SES factors did not mediate or moderate links between white matter and either working memory or inhibitory control. Conclusions: This work adds to a growing body of literature suggesting that the socioeconomic contexts in which children develop not only shape cognitive functioning and its underlying neurobiology, but may also shape the relations between brain and behavior. Abstract : In a diverse sample of 1082 children and adolescents aged 3–21 years, we examine socioeconomic disparities in white matter macrostructure and microstructure. We further investigate relations between family SES, children's white matter volume and integrity in tracts supporting EF, and performance on EF tasks.